Pengaruh Self-Acceptance Importance, Affiliation Importance, dan Community Feeling Importance terhadap Compulsive Buying - Euis Soliha (Jurnal Siasat Bisnis, 2010)
This study focused on phenomenon behavior of compulsive buying. The study examined how Self-Acceptance Importance, Affiliation Importance, and Community Feeling Importance influenced on Compulsive Buying. Population in this research was students in Kota Semarang, and 104 students become samples. To answer problem that is accurate, researcher applies econometrics Logit model. Result of research indicates that there were negativity influence Self-Acceptance Importance, Affiliation Importance and Community Feeling to Compulsive Buying. Result of this supports all hypothesis and consistent with theory.Keywords:    compulsive buying, self-acceptance Importance, affiliation Importance, community feeling Importance, Logit Model